Reimagining CO2 management: SWOT analysis and global outlook on CCUS and ICCU technologies - Sudhakaran, Amitha Kalappurakkal; Sreekantan, Sreejith; Marimuthu, Banu (Sustainable Chemistry for Climate Action, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">The persistent rise in atmospheric CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> levels, driven by industrialization and fossil fuel dependence, has made carbon dioxide a central target in global climate mitigation efforts. Despite its thermodynamic stability and linear geometry, which make its activation inherently difficult, CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> has long been identified as a major greenhouse gas since the mid-20th century. This review presents a comprehensive outlook on Carbon Capture, Utilization, and Storage (CCUS) technologies, with a focused discussion on Integrated Carbon Capture and Utilization (ICCU) approaches. We begin with a brief historical and scientific background on CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> as a greenhouse gas and the pressing need to curb emissions. A critical evaluation of various capture technologies-post-combustion, pre-combustion, oxy-fuel, and direct air capture is provided, highlighting their principles, merits, and limitations. The current global landscape of CCUS infrastructure, including pilot, commercial, and developing-scale operations, is summarized. A SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis is presented to assess the viability of CCUS pathways. Particular emphasis is placed on CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> capture mechanisms via absorption (liquid solvents like amines, amino acids, ILs, ammonia, and alkaline solutions) and adsorption (solid sorbents), followed by a detailed literature survey of solvent-based capture methods. Recognizing the isolated inefficiencies of standalone capture or utilization processes, the review underscores the emerging importance of ICCU strategies. Recent advancements in CO<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">2<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> conversion to methanol, methane, and formic acid via integrated systems are discussed, highlighting the synergy between capture and conversion units.

Upcycling solid wastes: using abundant egg shell wastes for the greener production of lactic acid under ambient conditions - Sreekantan, Sreejith; Sudhakaran, Amitha Kalappurakkal; Marimuthu, Banu (Journal of Environmental Chemical Engineering, 2025)
In this study, we explore a sustainable approach to repurposing eggshell waste as a catalyst for the conversion of biomass-derived sucrose, sugar syrup, xylan, and cellulose into lactic acid, a chemical in high demand. Currently, lactic acid is industrially produced using lactic acid bacteria (LAB), which require precise pH control and temperature maintenance, complicating their application. Our work demonstrates a one-pot synthesis of lactic acid using calcined eggshells in an aqueous medium via simple thermal treatment. Comprehensive characterization of the eggshell catalyst was carried out using techniques such as XRD, BET, FT-IR, FE-SEM, XPS, and TGA, revealing that calcination above 700 degrees C transformed the eggshell into CaO, drastically altering its morphology and enhancing its basicity. At 200 degrees C, using 70 wt% of catalyst for 1 h, we achieved a remarkable 92 C-mol% lactic acid yield with excellent carbon balance. The increased basicity played a key role in selectively driving lactic acid production. Our approach offers a green, sustainable solution with significant implications for future research in valorizing waste materials and advancing bio-based chemical production.
Keywords: Biomass; Lactic acid; Sustainability; Waste egg shell; Waste-to- chemicals